Síndrome vestibular periférica com paralisia unilateral de nervo facial relacionados ao hipotireoidismo em cão boxer - Galvão, André Luiz Baptista [UNESP]; Munhoz, Thiago Demarchi [UNESP]; Da Costa, Paula Ferreira [UNESP]; D'Angelo, Giuliana Tessari; Dos Santos Costa, Sabrina; De Vasconcellos, Amanda Leal [UNESP]; Karcher, Débora Emy [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2013)
The vestibular syndrome is a frequent ocurrence in clinical practice, particularly fo small animals. Clinical manifestations include head tilt, falling, rolling, walking in small circles, nystagmus, horner's syndrome, facial nerve paralysis and tremor. Peripheral vestibular disorders are more routine than the central, being described as possible causes otitis media, congenital diseases, aminoglycoside ototoxicity and hypothyroidism. The hypothyroidism can promote polyneuropathy in dogs with cranial nerve involvement, megaesophagus and laryngeal paralysis. The present report aims to describe a case of Boxer dog, six years old, with peripheral vestibular syndrome and unilateral facial nerve palsy due to hypothyroidism.
Peripheral vestibular syndrome with unilateral facial nerve paralysis associated hypothyroidism in boxer dog - Case report
Keywords: Hypercholesterolemia; Levothyroxine; Polyneuropathy